Calidad de vida y adherencia al tratamiento en pacientes con hipertensión arterial en el barrio Isidro Ayora Alto y Bajo - Saavedra Torres, Michael Vicente (2023)
Arterial hypertension is one of the chronic and cardiovascular disorders that most affect the adult population worldwide being one of the causes of early death, adherence to treatment along with quality of life are fundamental pillars in the adaptation of the patient to make changes in their lifestyle to improve their health. The present research aimed to determine the quality of life and therapeutic adherence in patients diagnosed with hypertension in Isidro Ayora Alto and Bajo neighborhoods of Loja during April-August 2022, with a quantitative approach, crosssectional cohort, had the participation of 60 people who met the inclusion and exclusion criteria, to whom the Minichal and Morisky Green test was applied, obtaining that 88.33% (n=53) have poor adherence to hypertensive treatment, 11. 67% (n=7) have a high quality of life; 55% (n=33) have a medium quality of life and 33.22% (n=20) have a low quality of life. We conclude that in this population there is a significant relationship (p<0.01) between adherence to hypertensive treatment and quality of life, this being a positive relationship: the greater the adherence, the greater the quality of life